(untitled) (Journal of Nuclear Technology in Applied Science, 2023)
Hepatitis D virus (HDV) infection is exceedingly pathogenic, and it aggravates the natural viral hepatitis B (HBV) infection by progressing to cirrhosis. Therefore, we aimed to ascertain the incidence, prevalence, and features of hepatitis B and/or D virus co-infection in individuals with renal impairment. A total of 92 renal patients were enrolled in the study between October 2017 and November 2021. Liver and kidney functions were assessed, and HBsAg, IgM anti-HDV, and total HDV antibodies were detected to determine HBV/HDV coinfection.We found that HBV/HDV coinfection is more common in patients with renal failure than in renal insufficiency. Furthermore, 26.1% (24 of a total 92) of patients with (HBV) renal failure and 5.4% (5 of a total 92) of individuals with (HBV) renal insufficiency showed antibodies to (HDV). HBV/HDV coinfection resides in rural areas than in urban ones. Alanine transaminase (ALT) is in the normal range, while aspartate transaminase (AST), total and direct bilirubin (T Bil), (D Bil), creatinine, uric acid, and urea serum levels, and Prothrombin time (PT) were high, and albumin (ALB) was decreased.In addition, the death rate in renal patients infected with virus 19 out of a total of 29 (virus B infection), including 13 co-infections with the virus. It is concluded that among the examined (HBV) & (HDV) renal patients, renal impairment may significantly increase the prevalence and incidence of hepatitis infection due to the weakening of the immune system of patients. If coinfection is not treated, this will result in 100% death.